2019
DOI: 10.1126/sciadv.aav7174
|View full text |Cite
|
Sign up to set email alerts
|

Dual-gradient enabled ultrafast biomimetic snapping of hydrogel materials

Abstract: The design of materials that can mimic the complex yet fast actuation phenomena in nature is important but challenging. Herein, we present a new paradigm for designing responsive hydrogel sheets that can exhibit ultrafast inverse snapping deformation. Dual-gradient structures of hydrogel sheets enable the accumulation of elastic energy in hydrogels by converting prestored energy and rapid reverse snapping (<1 s) to release the energy. By controlling the magnitude and location of energy prestored within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
182
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(185 citation statements)
references
References 36 publications
1
182
0
Order By: Relevance
“…Fan et al suggested the preparation of dual-gradient hydrogel materials, i.e., hydrogels with chain and cross-linking density gradients [13]. The dual-gradient should mimic fast actuation phenomena in nature such as the snapping leaves of a flytrap.…”
Section: Controlled Gelationmentioning
confidence: 99%
“…Fan et al suggested the preparation of dual-gradient hydrogel materials, i.e., hydrogels with chain and cross-linking density gradients [13]. The dual-gradient should mimic fast actuation phenomena in nature such as the snapping leaves of a flytrap.…”
Section: Controlled Gelationmentioning
confidence: 99%
“…Hydrogels with good flexibility and water‐storage performance belong to the class of highly promising functional materials. Their high hydrophilicity, water retention, and good biocompatibility endows them with extensive application prospects in biological tissue scaffold, controlled release of drug, adsorption and separation of pollutants, sensors, intelligent soft robots, petroleum engineering, mining engineering, and other fields. However, the traditional hydrogels are brittle.…”
Section: Introductionmentioning
confidence: 99%
“…To address the working environment limitation, the poly(acrylic acid‐ co ‐acrylamide) P(AAm‐ co ‐AAc) hydrogel was introduced on account of its opposite thermos‐responsiveness. Previous researches have reported some bilayer hydrogels which were composed of intelligent hydrogels with opposite responsiveness . As the temperature increases above the upper critical solution temperature of the P(AAm‐ co ‐AAc) hydrogel, the hydrogen bonds between PAAm and PAAc segments break and they form new hydrogen bonds with water molecules, respectively.…”
Section: Resultsmentioning
confidence: 99%